2017
DOI: 10.1039/c7ra10864h
|View full text |Cite
|
Sign up to set email alerts
|

Dual mode temperature sensing through luminescence lifetimes of F- and O-coordinated Cr3+sites in fluorosilicate glass-ceramics

Abstract: International audienceLuminescence lifetime based temperature sensing has an intrinsic immunity to the influence of external conditions, and dual mode thermometry is highly accurate due to its "self-calibration" merit. To develop thermometry with both features, we investigated the phase and microstructural evolution of Cr3+-doped calcium-fluorosilicate glass and glass-ceramics, which revealed different luminescent behavior relating to the different Cr3+ sites in the materials. From the photoluminescence (PL) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Here, C is the degeneration ratio with a value of 3, ΔE is the energy gap between the two excited states 2 E, 2 T 1 , and 4 T 2 , k B is the Boltzmann constant and T is the absolute temperature. By solving Equations ( and ), the temperature‐dependant lifetime can be calculated by the following equation: τ=τnormalE×1+3exp(ΔE/knormalBT)τEτT+3expfalse(normalΔnormalEfalse/kBTfalse)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, C is the degeneration ratio with a value of 3, ΔE is the energy gap between the two excited states 2 E, 2 T 1 , and 4 T 2 , k B is the Boltzmann constant and T is the absolute temperature. By solving Equations ( and ), the temperature‐dependant lifetime can be calculated by the following equation: τ=τnormalE×1+3exp(ΔE/knormalBT)τEτT+3expfalse(normalΔnormalEfalse/kBTfalse)…”
Section: Resultsmentioning
confidence: 99%
“…The Ln 3+ ‐doped based optical thermometers are primarily based on temperature correlated fluorescence intensity ratio (FIR) of thermally coupled energy levels, such as 2 H 11/2 and 4 S 3/2 of Er 3+ ions . Whereas, the TM ions‐doped optical thermometers are based on the temperature‐dependent fluorescence decay lifetime, such as chromium's (Cr 3+ ) fluorescence lifetime of the transition between two thermal coupled energy levels ( 2 E and 4 T 2 ) . FIR‐based thermometry has the intrinsic property of being independent from spectral losses and fluctuations and thus proven to be very accurate and reliable .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Ba 2 LaF 7 :Ln 3+ containing glass-ceramics have extraordinary UC luminescence property, being a potentially candidate for random lasing action, [4,5] optical thermometry, [6] and green phosphors in white light-emitting diodes. [9][10][11][12] Previous researches revealed that the unique connection between the chemical state of dopants and topology of the disordered glass structure in oxide glass system. [8] Different luminescent centers have coordination preferences in oxide or fluoride environment.…”
Section: Introductionmentioning
confidence: 99%
“…Different luminescent centers have coordination preferences in oxide or fluoride environment. Normally, most of the Ln 3+ is found to enrich in the fluoride phase, while the transition metal ions can enrich in the oxide or fluoride phase depending on other glass modifier cations in the composition . Previous researches revealed that the unique connection between the chemical state of dopants and topology of the disordered glass structure in oxide glass system .…”
Section: Introductionmentioning
confidence: 99%
“…In response to the requirements imposed by technology, micro/nanoelectronics or photonics as well as by biomedical applications, new approaches to the luminescent nanothermometers (LNTs) have to be proposed to secure fast and accurate temperature sensing with submicrometer spatial resolution, and highly sensitive temperature readout (Brites et al, 2012; Jaque and Vetrone, 2012; Chen et al, 2016; del Rosal et al, 2016a,b; Dramićanin, 2016; Marciniak et al, 2016b; Suo et al, 2017; Wang et al, 2017; Gao et al, 2018; Liao et al, 2018; Liu et al, 2018; Malysa et al, 2018; Runowski et al, 2018; Zhong et al, 2018). One of the most promising one, relies on exploiting transition metal (TM) ions, whose highly temperature dependent emission is referred to emission of barely temperature dependent lanthanides ions (Marciniak et al, 2017a; Drabik et al, 2018; Elzbieciak et al, 2018; Kniec and Marciniak, 2018; Marciniak and Trejgis, 2018; Trejgis and Marciniak, 2018).…”
Section: Introductionmentioning
confidence: 99%